Enforcing Mobile Application Blocking in India: A Technological Analysis - Sachdeva, Pankaj; Meena, Ravi Krishan (Journal of Advanced Research in Electronics Engineering and Technology, 2025)
The Government of India has initiated several measures to safeguard digital sovereignty, one of the most notable being the blocking of mobile applications considered prejudicial to national security. While the policy declarations are swift and assertive, enforcement remains a grey area plagued by technological loopholes and regulatory challenges. This paper explores the enforcement process of mobile application bans in India, analyses the inefficiencies in its current structure, and proposes a comprehensive set of recommendations for strengthening the enforcement mechanism. Emphasis is also placed on the role of mobile OS providers, the circumvention techniques used by users, and the lack of real-time monitoring tools for compliance. The paper suggests a multipronged approach integrating law, technology, and awareness to make the ban process more effective and secure.